NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI MAPPANRETASI DI DESA WIRITASI KELURAHAN PAGATAN KECAMATAN KUSAN HILIR KABUPATEN TANAH BUMBU - Habriani, Habriani (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
This study discusses the values ​​of Islamic education in the Mappanretasi tradition in the village of Watanasi Pagatan Village, Kusan Hilir Subdistrict, Tanah Bumbu Regency. This study aims to find out why the villagers of Wiritasi do the Mappanretasi tradition, how the process of implementing the Mappanretasi tradition goes, and what Islamic education values ​​are contained in the Mappanretasi tradition. Subjects in this study are all components involved in the tradition of Mappanretasi, especially the board of the Ade 'Ogi Tanah Bumbu (LAOTU) as authorized and responsible in the implementation of the tradition. The objects in this study are the values ​​of Islamic education in the Mappanretasi tradition. Data mining techniques, which are used are observation techniques, interviews, and documentation. The data processing technique is done by editing and data classification. Further analyzed by qualitative descriptive analysis and the inductive conclusion drawn. Based on the results of the research note that the values ​​of Islamic education in Mappanretasi tradition in the village of Writasi, in general, is true there, this can be seen from the understanding of Mappanretasi and the process of implementation of Mappanretasi tradition such as Mappammulagau Mappanretasi ritual, Maddemme Berre, Mallibu Wanuwa, all of which contain elements of Islamic education. Through this tradition also proves that education, especially Islamic education is not absolutely obtained through formal institutions, but also from the forms that hold meaning for the life of the people as is done by the villagers Wiritasi. The findings of this study indicate at least this tradition can be an alternative solution and provide a positive influence to the community especially for the development and improvement of Islamic education. Keywords: Value, Islamic Education, Mappanretasi Tradition.